If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + -3) = 6(x + -1) + 4x Reorder the terms: 5(-3 + 2x) = 6(x + -1) + 4x (-3 * 5 + 2x * 5) = 6(x + -1) + 4x (-15 + 10x) = 6(x + -1) + 4x Reorder the terms: -15 + 10x = 6(-1 + x) + 4x -15 + 10x = (-1 * 6 + x * 6) + 4x -15 + 10x = (-6 + 6x) + 4x Combine like terms: 6x + 4x = 10x -15 + 10x = -6 + 10x Add '-10x' to each side of the equation. -15 + 10x + -10x = -6 + 10x + -10x Combine like terms: 10x + -10x = 0 -15 + 0 = -6 + 10x + -10x -15 = -6 + 10x + -10x Combine like terms: 10x + -10x = 0 -15 = -6 + 0 -15 = -6 Solving -15 = -6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| .25*-7+3=x | | 4n=16(n+12) | | 25c^2-80c+64=0 | | -3x-42= | | 7-3x=-2 | | x^3+10x^2=0 | | 2(1-4n)=34-4n | | 4y=2.6 | | 3x-2(-6-11)=-113 | | 15(k+3)-k=20 | | 3x+7+6x+20=90 | | 8x^2+112x=0 | | 3x-2+6x=-56 | | 2(x+y)+6n(x+y)=0 | | 5x^2-5xy= | | 2(2c+10)-c=-13 | | 3x+9=3x+9 | | 6(x-6)+4=8(x+2)-6 | | 0=16a^2-8a-3 | | -6a=21 | | 4u^2-1=0 | | y=y | | -18+24+(-14)= | | 0-3=x | | 20+2x=-(x-4)+5x | | -6-3=x | | 4n+5-9n=5(n+2)-10n | | 10-5x-5x=-90 | | (6x+1)-3=12x+(8x-4) | | -7-3=x | | -22-(-56)= | | 3(x-1)=3x |